Integrating Madurese Indigenous Philosophy Into Sustainable Business Framework: A Model For Warung Madura Resilience - Abdul Azis; Vika Annisa Qurrata; Thomas Sosecco (CV. Doki Course and Training, 2026)
This study examines the influence of Madurese ethnic philosophy on the business sustainability of Madura stalls, emphasizing cultural values as strategic capital that strengthens resilience. Core cultural principles including tretan dhibi’ (based solidarity), honesty, perseverance, and a strong work ethic shape management practices, trust mechanisms, and social networks that enhance competitive advantage. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), with 257 Madurese stall owners selected through the Slovin formula. The results of the outer model indicate that all indicators meet the required validity and reliability criteria. The inner model reveals an R² value of 0.337, indicating that Madurese ethnic philosophy significantly contributes 33.7% to business sustainability. These findings demonstrate that Madurese philosophy serves not only as a moral guideline but also as a form of social capital that facilitates supply stability, operational efficiency, trust-based networks, and the psychological resilience of business owners. The study underscores that local wisdom functions as a strategic asset in strengthening the sustainability of microenterprises and must be integrated with modern innovation to maintain competitiveness in an evolving market landscape.